Vascular development analysis: a study for tertiary anti-vascular endothelial growth factor therapy after second reactivation of retinopathy of prematurity - Zhang, Xuerui; Peng, Jie; Yang, Yuan; Liu, Yongqing; Zhang, Wenting; Gu, Victoria Y.; Liu, Huanyu; Xiao, Haodong; Yin, Jiawei; Xu, Yu; Zhao, Peiquan (Frontiers in Medicine, 2024)
Purpose To observe the vascular development results of tertiary anti-vascular endothelial growth factor (anti-VEGF) therapy following spontaneous second reactivation of retinopathy of prematurity (ROP). Methods This retrospective study included 22 infants (42 eyes) with Type 1 or aggressive ROP (A-ROP) who received three anti-VEGF drug treatments for ROP from January 2018 to December 2022. The vascular growth, possible associated risk factors, and the retinal vascularization (DB/DF ratio) were assessed. Results The mean follow-up was 17.6 months. After the 3rd intravitreal injection, seven eyes showed complete vascularization (Group 1), while the remaining 35 eyes demonstrated persistent avascular retina (PAR) (Group 2). In Group 2, 17 eyes maintained a stable state and were classified in the regression subgroup. The other 18 eyes developed a 3rd reactivation (reactivation subgroup) and were treated with laser photocoagulation (LPC). Birth weight (BW) was significantly lower in Group 2 than in Group 1 (p < 0.001). The decision tree analysis shows that only infants weighing more than 1,250 g (17.50%) had a chance to achieve complete retinal vascularization. The possibility of PAR was higher in patients with BW <1,250 g than ≥1,250 g (70.00% vs. 12.50%). In addition, most infants with BW ≥ 1,290 g and initial ROP disease in Zone I or posterior Zone II developed PAR. Conclusion Tertiary IVR can successfully treat a second ROP reactivation and improve peripheral retinal vascularization. BW is the most significant factor related to complete retinal vascularization. Our decision tree model may be helpful in predicting the prognosis of anti-VEGF drugs in the event of a second ROP reactivation.